Moss mites (Acari, Oribatida) at the edges of bog lakes and pools in Brodnica Lakeland and Orawa–Nowy-Targ Basin (Poland) - Seniczak, Anna; Seniczak, Stanisław; Mistrzak, Marcin; Nowicka, Anna; Krasicka-Korczyńska, Ewa (Biological Letters, 2014)
Moss mites were investigated at the edges of 4 bodies of water located in bogs: 2 lakes in Brodnica Lakeland (O and S) and 2 pools in Orawa-Nowy-Targ Basin (K and LP). The lakes differed from the pools in most of the analysed physicochemical parameters of water and in plant associations growing at their edges. Consequently, the species richness of Oribatida and their species composition differed between lakes and pools, but the total abundance of mites was similar. Abundance of most species was low, and only 13 had dominance indices (D) exceeding 1%. The acarofauna of both lakes was similar, as most abundant in them was Limnozetes foveolatus (D > 80%), and relatively abundant were Hydrozetes longisetosus, Limnozetes ciliatus, Punctoribates sellnicki, and Trhypochthonius nigricans. These species were absent or rare at the edges of pools K and LP. In the pools, differences in species structure of Oribatida were observed. At pool K, Trimalaconothrus maior was most abundant, accompanied by Hydrozetes octosetosus, H. lacustris, and Limnozetes foveolatus. At pool LP, Trimalaconothrus foveolatus was most abundant, which tolerates a wider range of humidity than T. maior; relatively abundant were also T. maior, Hydrozetes lacustris, and several species that were not found in the other bodies of water, including a generalist like Oppiella nova. In this study, Liochthonius furcillatus and Cultroribula berolina were recorded for the first time from Poland.